Combined pelvic and femoral reconstruction in children with cerebral palsy. Issue 1 (January 2018) - Alassaf, Nabil; Saran, Neil; Benaroch, Theirry; Hamdy, Reggie Cherine
Objective: The primary aim of this study was to determine the effect of age, femoral head migration, and ambulatory status on radiographic outcomes after combined pelvic and femoral reconstruction in children with cerebral palsy. The secondary aim was to evaluate the fate of the opposite hip after unilateral reconstruction. Methods: A retrospective cohort study design of consecutive patients from 1995–2009 was used. The records were screened for patients who underwent varus derotational osteotomy and modified Dega osteotomy. Results: Eighty-five hips in 71 patients were included. The mean age was 8.4 ± 3.2 years and the mean follow-up was 6.6 ± 3.1 years. The final measures were a mean migration index of 20% ± 15.58%, centre edge angle of 28.45° ± 15.98°, and Sharp's angle of 40.75° ± 8.5°. Those values were not correlated with age and the initial migration index. Nonambulatory status did not negatively affect hip stability. Final measurements of the contralateral hips were similar to the reconstructed hips, and the cumulative incidence for later reconstruction was 5.67%. Conclusions: Regardless of age, preoperative displacement, and ambulation, the combined procedure provides durable radiographic improvement. In unilateral cases, there is a low risk of later deterioration of the opposite side.